Wintering steer calves on alfalfa silage. - Cox, R.F.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Eighteen good quality Hereford steer calves were used in the test. They were part of a group of 150 steer calves obtained from Marfa, Texas, for experimental purposes. They were divided into two lots of 3 head each and started on test December 22, 1951. Both lots were given free access to a mineral mixture and salt. Lot 1 was fed nonwilted alfalfa silage, and Lot 2 was fed wilted alfalfa silage. No preservation was added to either silage. Each type of silage was stored separately in small tile silos. The silage was made from second cutting alfalfa approaching bloom. The nonwilted silage was somewhat more mature than the wilted silage. The calves were fed all of the silage they would eat twice daily.
Keywords: Beef; Steers; Alfalfa silage; Alfalfa hay